1992
DOI: 10.3109/02770909209099022
|View full text |Cite
|
Sign up to set email alerts
|

Airway Mucosal Inflammation

Abstract: Eosinophils and lymphocytes in tuberculin and allergen-induced skin reactions in atopic and non-atopic subjects. J

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…We found that in contrast to normal subjects neither exhaled LTB 4 nor exhaled NO levels increase after sputum induction in asthmatic patients. Infl ammation of the airway mucosa is a cardinal feature of clinical asthma [20] . This is supported in the present study by increased levels of exhaled NO in asthmatic patients compared with normal subjects, as previously reported [21] .…”
Section: Discussionmentioning
confidence: 99%
“…We found that in contrast to normal subjects neither exhaled LTB 4 nor exhaled NO levels increase after sputum induction in asthmatic patients. Infl ammation of the airway mucosa is a cardinal feature of clinical asthma [20] . This is supported in the present study by increased levels of exhaled NO in asthmatic patients compared with normal subjects, as previously reported [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Typically not much more than 20% of the dose will be delivered to the conducting and respiratory airways, with these particles depositing throughout the airways . Deposition in the peripheral airways tends to occur for particles below about 5 microns . Particles depositing in the upper airways, or tracheal and bronchial regions, are usually cleared from these regions via mucociliary clearance over the course of several hours. , Much of the dose, especially the larger particles, will deposit in the mouth and throat and will be swallowed.…”
Section: Role Of Particles In Orally Inhaled Drug Productsmentioning
confidence: 99%